School Travel Inequity between Students from Public and Private Schools in the City of Shenzhen, China. (18th November 2021) - Xiao, Zuopeng; Lin, Taoyu; Liao, Jingying; Lin, Yaoyu
Abstract : Understanding school travel inequities and promoting active travel policies more effectively is an increasingly important issue in the international transport policy agenda. Using the dataset of the 2014 Shenzhen primary and secondary school travel survey, this study empirically revealed the permanent residence permit ( hukou ) system in the context of China shapes the evident inequities between students from public schools and private schools. Students without a legitimated hukou to local areas suffer from more constraints, longer distances, and more time to access private schools which are excluded from the public sponsorship and have disadvantages in geographical locations. Applying the ordered logistic model, this study specifically investigated the influential factors of school commuting travel mode. Household vehicle ownership and travel features (i.e., chauffeuring and home-school distance) have a much more significant role in school travel mode decisions, which largely surpassed the role individual demographic attributes and the school surrounding built environment play. The implications of this study shed light on making more specific strategies for private schools to mitigate mobility inequity imposed on disadvantaged students.